Effects of IL-1β and TNF-α on the Expression of P311 in Vascular Endothelial Cells and Wound Healing in Mice - Zhou, Daijun; Liu, Tengfei; Wang, Song; He, Weifeng; Qian, Wei; Luo, Gaoxing (Frontiers in Physiology, 2020)
Objective: This study aimed to define the role of IL-1β and TNF-α in the expression of P311 in VEC and in wound healing. Methods: DAPI staining, CCK-8 assay, cell migration assay and angiogenesis assay were used to assess the effects exerted by TNF-α and IL-1β at various concentrations on morphology, proliferation, migration, and angiogenesis of vascular endothelial cells. WB and RT-PCR models were employed to observe the effects exerted by proteins related to the NF-κB signaling pathway and P311 mRNA expression. Bioinformatics analysis was performed on the binding sites of P311 and NF-κB. Finally, to investigate the effects of IL-1β and TNF-α on wound healing and length of new epithelium in mice, we established a full-thickness wound defect model in mice. Immunohistochemistry was used to measure changes in P311, PCNA, VEGF, CD31, as well as other related proteins. Results: When levels of TNF-α and IL-1β were both 20 ng/ml, their effects on cell proliferation, cytoskeleton protein expression, cell migration and angiogenesis were the greatest (P<0.05). IL-1β and TNF-α at moderate concentrations effectively promoted P311 mRNA and p-NF-κB protein expression (P<0.05), while p- NF-Κb protein expression was decreased (P<0.05). Luciferase assays showed that P311 expression was also relatively greater when stimulated at moderate concentrations (P<0.05), while relative expression was significantly lower when p- NF-Κb inhibitor CAPE was added (P<0.05). On 7-day wound healing rate comparison, the control, IL-1β, IL-1βab, TNF-α, and TNF- αab groups were 18%, 37%, 35%, 39%, 36%, respectively, while control group +P311 siRNA was 31% (P<0.05). New epithelial length, granulation tissue thickness, and number of blood vessels trends were also the same. In the control group, P311 showed lower relative expression levels than the others (P<0.05). P311 relative expression levels trended as follows: control group > IL-1βab > IL-1β> TNF- αab > TNF-α(P<0.05).Conclusions: IL-1β and TNF-α can effectively promote the proliferation, expression, migration and angiogenesis of vascular endothelial cells by promoting the expression of the NF-Κb pathway and thereby promoting the expression of P311. In vitro experiments on mice suggest that P311 effectively promotes wound healing, and its mechanism may be closely related to PCNA, CD31, and VEGF.